A process-focused case series of a school-based intervention aimed at giving young people choice and control over their attendance and their goals in therapy. Issue 4 (4th July 2021) - Churchman, Anamaria; Mansell, Warren; Tai, Sara
ABSTRACT: This study investigated clinical and process factors involved in a client-led psychological intervention (Method of Levels therapy – MOL). MOL offered 16 adolescents choice and control over attendance (by using a self-booking system) and topics discussed in sessions. Process measures examining empowerment and ability to resolve psychological conflict were used to explore the impact MOL might have on these. Young people booked a wide-ranging number of sessions at differing intervals and set goals related to their emotional or mental wellbeing. On completion, the majority of adolescents displayed an increase in scores for empowerment and ability to resolve psychological conflict and overall distress levels decreased. Benefits were sustained two months after completion of the study.